ANALISIS PEMBIAYAAN MUDHARABAH DAN MURABAHAH (STUDI KASUS BRI SYARIAH CABANG GUBENG SURABAYA) - Pradana, Yurista (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this research is to determine system and concept of mudharabah and murabahah financing in BRI Syariah branches Gubeng Surabaya and to determine whether the practice field (mudharabah and murabahah) in accordance with the theory or rules and regulations. The research used a qualitative method in which researchers set of a phenomenon instead of a theory. The results of this research are mudharabah and murabahah products in BRI Syariah branch Gubeng Surabaya was appropriate or comply with the rules DSN-MUI in force.Keywords : Mudharabah, Murabahah, BRI Syariah branch Gubeng Surabaya, DSN-MUI